Need Analysis on English for Tourism Subject of English Students at Universitas Banten Jaya - Miftah Komala Putri; Fadilla Oktaviana; Dini Fitriani (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this research is to explore the need analysis on English for Tourism Subject of English Student at Universitas Banten Jaya. This research was Descriptive Quantitatve research by using survey method. This research used Google Form as questionnaire to gain the data. The respondents of this research are English students at Universitas Banten Jaya. The result of this research was 67% which categorized as agree that English for Tourism Subject as additonal subject for students at Universitas Banten Jaya majoring English Education Study Program. The reasons were based on several beneficial aspect from studying English for Tourism such as Banten have many potencial aspect of tourism; EFT as interesting subject matter; The importance role of english for tourism in Banten; by learning EFT can bring students’ understanding and comprehension in cultural terms through interaction with tourists and local tourists improved, It develop students in a critical and theoretical understanding, English plays a vital role in the Indonesian tourism industry; and last, by studying EFT, it can create the spirit of entrepreneurship. In short, EFT recommended as additional subject matter in Banten generally, and especially for students in English Education Study Program, Universitas Banten Jaya.